2004
DOI: 10.1186/ar1209
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating levels and salivary gland expression of interleukin-18 in patients with Sjögren's syndrome: relationship with autoantibody production and lymphoid organization of the periductal inflammatory infiltrate

Abstract: IL-18, an immunoregulatory and proinflammatory cytokine, has been shown to play an important pathogenic role in Th1-driven autoimmune disorders. In this study, we evaluated the circulating levels and salivary-gland expression of IL-18 in patients with Sjögren's syndrome (SS), a mainly Th1-mediated disease. IL-18 serum levels were measured by ELISA in 37 patients with primary SS, 42 with rheumatoid arthritis, and 21 normal controls. We demonstrated high IL-18 serum levels in SS, similar to those in rheumatoid a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(45 citation statements)
references
References 53 publications
(64 reference statements)
2
43
0
Order By: Relevance
“…Ductal epithelial cells of SS patients have been also reported to express in situ high levels of IL-12 [20] and mature-type IL-18 [21], although these findings were not corroborated by another study. In addition, the expression of several T-cell-attracting and germinal-center-forming chemokines has been detected in ductal epithelia, including CCL3/MIP1a, CCL4/MIP-1b, IL-8 and CCL5/RANTES [22], STCP-1/ MDC, CXCL-9/Mig, CXCL-10/IP-10, CXCL12/SDF-1, CCL17/TARC, CXCL13/BCA-1, and CCL19/ELC and CCL21/SLC/TCA [23][24][25][26][27].…”
Section: In Situ Activation Of Epithelial Cells In Sjögren's Syndromementioning
confidence: 84%
“…Ductal epithelial cells of SS patients have been also reported to express in situ high levels of IL-12 [20] and mature-type IL-18 [21], although these findings were not corroborated by another study. In addition, the expression of several T-cell-attracting and germinal-center-forming chemokines has been detected in ductal epithelia, including CCL3/MIP1a, CCL4/MIP-1b, IL-8 and CCL5/RANTES [22], STCP-1/ MDC, CXCL-9/Mig, CXCL-10/IP-10, CXCL12/SDF-1, CCL17/TARC, CXCL13/BCA-1, and CCL19/ELC and CCL21/SLC/TCA [23][24][25][26][27].…”
Section: In Situ Activation Of Epithelial Cells In Sjögren's Syndromementioning
confidence: 84%
“…IL-12 supplied by APC and/or IL-18 and possibly IL-21 cooperate to promote IFNg production by activated T cells [66]. Increased concentrations of IFNg contribute to the upregulation of HLA class II [65] and costimulatory molecules [19] on epithelial cells and APC.…”
Section: Ifngmentioning
confidence: 99%
“…For example, Lienesch et al (17) and Orge et al (18) found no increase in anti-CCP in non-arthritic patients with chronic HCV infection. Similarly Bombardieri et al (19) examined RF and anti-CCP in patients with chronic HCV infection and found RF positivity in 37% of the patients vs. no patients with anti-CCP positivity.…”
Section: Discussionmentioning
confidence: 94%